Pendekatan Ekspositori Kajian Kitab Kejadian 2:24 Hubungan Suami-Istri Sebagai Fondasi Pemahaman Gereja Sebagai Komunitas yang Terhubung Dalam Kristus - Erlangga Saputra; Malik Bambangan (LPPM - STT Kadesi Bogor, 2025)
This study explores the expository way of reading Genesis 2:24, which discusses the relationship between husband and wife as the basis for understanding the church as a united community in Christ. The basic principle of marriage, the union of husband and wife that forms one flesh, is expressed there. Theology considers marriage to be a spiritual and social relationship that reflects Christ's relationship with the church. Expository text analysis and exegesis methods were used in this study. The study also considers the cultural and historical context of the creation period, as well as how the principle of marriage is applied to modern church life. This study shows that Christian marriage is based on love, unity, and commitment, as well as how important it is to maintain fidelity in the husband-wife relationship. This relationship reflects the relationship between Christ and the church. Therefore, marriage serves as an important pillar in the life of the church, providing strength. Therefore, marriage serves as an important foundation in the life of the church and helps to form a connected Christian community in Christ.